Clinical and molecular epidemiology of beta-hemolytic streptococcal infections in India - Purva Mathur; Nidhi Bhardwaj; Kushal Mathur; Bijayini Behera; Gunjan Gupta; Arti Kapil; Sarman Singh; Mahesh Chandra Misra (Journal of Infection in Developing Countries)
Introduction: Beta-hemolytic streptococci (βHS) cause a diverse array of human infections. Despite the high number of cases of streptococcal carriers and diseases, studies discerning the molecular epidemiology of βHS in India are limited. This study reports the molecular and clinical epidemiology of beta-hemolytic streptococcal infections from two geographically distinct regions of India. Methodology: A total of 186 isolates of βHS from north and south India were included. The isolates were identified to species level and subjected to antimicrobial susceptibility testing. Polymerase chain reaction (PCR) was done to detect exotoxin genes, and emm types of group A streptococci (GAS) strains were ascertained by sequencing. Results: GAS was the most common isolate (71.5%), followed by group G streptococci (GGS) (21%). A large proportion of GAS produced speB (97%), smeZ (89%), speF (91%), and speG (84%). SmeZ was produced by 21% and 50% of GGS and GGS, respectively. A total of 45 different emm types/subtypes were seen in GAS, with emm 11 being the most common. Resistance to tetracycline (73%) and erythromycin (34.5%) was commonly seen in GAS. Conclusions: A high diversity of emm types was seen in Indian GAS isolates with high macrolide and tetracycline resistance. SpeA was less commonly seen in Indian GAS isolates. There was no association between disease severity and exotoxin gene production.